PENERAPAN MODEL PEMBELAJARAN INKUIRI TERHADAP PENINGKATAN MINAT BACA SISWA KELAS VII A DALAM MATA PELAJARAN AKIDAH AKHLAK DI MTS CINA - Andi Sri Bulan; Nurul Adni; Almaghfira Nurul Fiqri; Nurul Mutmainna (Atta'dib Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the effect of the inquiry learning model on students' reading interest. Reading interest referred to in this study, namely the level of achievement of students in understanding the material as measured through observations made by researchers. This type of research is classroom action research, where the researcher acts as a teacher and observer. This research design is one part of the cooperative learning model. This research was conducted in the odd semester of the 2021/2022 academic year, namely in November at MTs China. The population consists of 30 students and the research sample is 11 students of class VII A MTs China, the object of research is students' reading interest. Data collection techniques using tests, observations, and questionnaires. The data analysis technique used is descriptive data analysis. The results showed a significant increase in students' reading interest, it can be seen from the increase experienced by the three assessment indicators. Namely: the feeling of pleasure of students increased from 5 students to 11 students, interest increased from 4 students to 9 students, and finally the attention of students increased from 9 students to 11 students.Keywords: interest in learning, inquiry learning model